Kort, knapp eller kantig? : Något om expressionism och prosa i Norden 1910–1930 - Hermansson , Gunilla (Tidskrift för litteraturvetenskap, 2013)
Short, Terse or Angular? Notes on Expressionism and Prose in the Nordic Countries 1910–1930 With Pär Lagerkvist’s earliest collections of short prose, Motiv (1914) and Järn och människor (1915) as a point of reference, the article discusses ”shortness” in relation to the problems of defining expressionist prose. Most researchers agree that expressionist prose is, first and foremost, short, with the argument that the expressionist intensity or tendency towards abstraction works against a narrative pace. However, in examining how authors critically concerned with expressionism in Germany, as well as in the Nordic countries, create and imagine an expressionist or modern prose, it becomes obvious that shortness is not a dominant requirement or idea. It is at least equally important to note that authors often strive to achieve inter-medial effects: aspiring, for instance, to the angularity, hardness and abstraction of cubist art, or to the tempo and technique of modern film. It also becomes evident that the term ”expressionist” needs to be more carefully applied in the Nordic than in the German context, in order to be meaningful. In the end, the concept of ”shortness” per se, does not aid in the definition of expressionist prose. Moreover, it cannot be concluded that Nordic authors utilize short forms in their literary experiments more consistently than they use longer forms. However, it is apparent that Lagerkvist is extremely attentive to the different effects of reducing or expanding his texts, particularly in order to let his readers see and see beyond the ”angularity” of his art.